1999
DOI: 10.1523/jneurosci.19-13-05619.1999
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Brain-Derived Neurotrophic Factor in Slices from Rats with Spontaneous Seizures and Mossy Fiber Sprouting in the Dentate Gyrus

Abstract: This study examined the acute actions of brain-derived neurotrophic factor (BDNF) in the rat dentate gyrus after seizures, because previous studies have shown that BDNF has acute effects on dentate granule cell synaptic transmission, and other studies have demonstrated that BDNF expression increases in granule cells after seizures.Pilocarpine-treated rats were studied because they not only have seizures and increased BDNF expression in granule cells, but they also have reorganization of granule cell "mossy fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 113 publications
(104 reference statements)
7
60
0
Order By: Relevance
“…All glassware and pipette tips were rinsed in 0.005% bovine albumin before use of BDNF. Previous studies in our laboratory showed that bovine albumin alone did not have detectable effects on hippocampal physiology in either normal or epileptic rats (Scharfman, 1997;Croll et al, 1999;Scharfman et al, 1999). …”
mentioning
confidence: 78%
See 2 more Smart Citations
“…All glassware and pipette tips were rinsed in 0.005% bovine albumin before use of BDNF. Previous studies in our laboratory showed that bovine albumin alone did not have detectable effects on hippocampal physiology in either normal or epileptic rats (Scharfman, 1997;Croll et al, 1999;Scharfman et al, 1999). …”
mentioning
confidence: 78%
“…Not only do they contain glutamate, but they also contain BDNF, NPY, and other substances. Although BDNF appears to enhance mossy fiber transmission (Scharfman, 1997;Scharfman et al, 1999), NPY has been shown to have primarily inhibitory effects on synaptic transmission (Vezzani et al, 1999b; but see also Gariboldi et al, 1998).…”
Section: Physiological Asymmetries and Their Relationship To Anatomicmentioning
confidence: 99%
See 1 more Smart Citation
“…NPY expression was found markedly increased in hilar GABAergic interneurons, granule cells and sprouted mossy fibers (Bellmann et al, 1991;Chafetz et al, 1995;Lurton and Cavalheiro, 1997;Scharfman et al, 1999Scharfman et al, , 2002Sperk et al, 1992;Takahashi et al, 2000;Vezzani et al, 1996). NPY in the dentate gyrus can influence synaptic transmission and neurogenesis, demonstrates remarkable plasticity after seizures (Scharfman and Gray, 2006), and may have an anticonvulsive action (Furtinger et al, 2001;Klapstein and Colmers, 1997;Vezzani et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF may promote it, NPY may reduce it. Indeed, BDNF does appear to facilitate seizure-like activity due to mossy fiber actions in animal models of epilepsy [149], and in similar epileptic rats NPY is tonically released and inhibits mossy fiber transmission in rats with chronic seizures [150]. Thus, the cascade of estrogen-BDNF-NPY may regulate seizures much more than previously considered.…”
Section: Epilepsymentioning
confidence: 98%